Fish-oil supplementation improves retinal injury induced by diabetes and hypercholesterolemia in male Wistar rats. Issue 1 (1st January 2020) - El-Sayyad, Hassan IH; Ali, Doaa A.; Hanafy, Mohamed E
ABSTRACT: Diabetes and hypercholesterolemia are metabolic diseases associated with impairment of vision. This work is done to illustrate the capacity of fish oil to improve the retinopathy of diabetes and hypercholesterolemia. Diabetes was induced by streptozotocin (60 mg/kg single dose in citrate buffer pH4.6 in combination with nicotinamide 100 mg/kg body weight). Hypercholesterolemia was induced by feeding rats on 3% cholesterol diet. Fish oil was supplemented orally every other day at 100 mg/kg body weight. Adult male Wistar albino rats 100 g.body weight were divided into 8 groups (n = 10); control, diabetes and/or hypercholesterolemia, with or without fish-oil treatment (100 mg/kg.body weight). After 12 weeks-treatment, animals were sacrificed and the ocular region was separated and subjected to investigation. Diabetes and/-or hypercholesterolemia reduced the levels of dopamine and serotonin and increase glycation end products, VEGF, ICAM-I& VCAM-I, caspases 3&7 and 8-deoxyhydroxyguanosine reflecting retinal cell damage. The damaged retinal cells showed increased immune reaction of GFAP, caspase 3 and single-cell strand DNA damaged retinal cells. Fish-oil supplementation decreased the assayed apoptic markers, managed retinal neurotransmitters, and improved histo-cytological pictures. The authors concluded that fish-oil supplementation improved the diabetes and hypercholesterolemia caused neovascularization and injuries to retinal cells due to its contents of antioxidant activity which scavenge the free radicals.